Integration of Islamic Law in Constitutional Judicial Review: Comparative Perspectives from Indonesia and Turkey - Mustakim Mustakim; Mas Subagyo Eko Prasetyo; Dayanto Dayanto; Kartika Sekar Jingga (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
: This article examines the integration of Islamic law within constitutional judicial review through a comparative analysis of the Constitutional Court of Indonesia and the Constitutional Court of Türkiye. The study addresses a significant gap in comparative constitutional scholarship concerning how Islamic legal values are incorporated into constitutional interpretation and judicial reasoning across contrasting constitutional models in Muslim-majority democracies. Employing normative legal research, the study combines comparative and conceptual approaches to analyze constitutional provisions, constitutional court decisions, and legal doctrines relating to constitutional supremacy, legal pluralism, secularism (laiklik), proportionality, and constitutional identity. The findings demonstrate that Indonesia adopts an implicit-accommodative model in which Islamic values are integrated indirectly through teleological, sociological, historical, and systematic constitutional interpretation without positioning sharia as a formal constitutional standard of review. Islamic norms function primarily as socio-constitutional values embedded within judicial reasoning and balancing mechanisms. In contrast, Türkiye historically applies a restrictive-exclusionary model grounded in Kemalist secularism, where Islamic law is generally treated as a potential threat to constitutional order under the doctrine of militant democracy. Nevertheless, recent constitutional developments reveal a gradual transition toward pragmatic accommodation through the proportionality test and the margin of appreciation doctrine influenced by European human rights jurisprudence. The study argues that constitutional identity and interpretive methodology are decisive variables shaping the scope of Islamic law integration in constitutional adjudication. By comparing Indonesia’s pluralistic-religious constitutionalism with Türkiye’s assertive secular constitutionalism, this article contributes to comparative constitutional theory by demonstrating that judicial review in Muslim-majority states operates along a dynamic spectrum between accommodation and exclusion rather than within a binary opposition between secularism and sharia. The study further offers a conceptual framework for understanding how constitutional courts mediate tensions between religious norms, democratic governance, and constitutional supremacy in contemporary Muslim societie